Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Modulation of the nanoscale chimney effect in metal–organic frameworks enables efficient guest diffusion and separation - Sha-Sha Meng; Hanxi Guan; Han Yang; Hai-Yue Wei; Mo-Han Gu; Jian Zhang; Ming Xu; Lina Wu; Zhi-Yuan Gu (Science Bulletin, 2026)

A fully self-breathing, liquid metal-fed, solid oxide cell for high-density energy storage - Xin Gu; Yidong Jiang; Chaojun Liu; Peidong Song; Wenfei Mo; Qiaoxia Zhu; Yaowei Hao; Xiaoyi Liu; Meng Han; Yixiang Shi; Ningsheng Cai; Zongping Shao (Chemical Engineering Journal, 2026)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Promoting the catalytic performance by tungstophosphoric acid modification Fe0.15Ce0.85 bimetal oxide catalysts for NH3-SCR - Chengheng Huang; Shifei Gu; Qiuju Qin; Xiaorong Han; Donghai Mo; Zhengjun Chen; Bin Li; Hongyan Zhang; Lihui Dong (Fuel, 2025)

Crosstalk among proximal tubular cells, macrophages, and fibroblasts in acute kidney injury: single-cell profiling from the perspective of ferroptosis - Yulin Wang; Ziyan Shen; Shaocong Mo; Han Zhang; Jing Chen; Cheng Zhu; Shiqi Lv; Di Zhang; Xinhui Huang; Yulu Gu; Xixi Yu; Xiaoqiang Ding; et al. (Human Cell, 2024)
The link between ferroptosis, a form of cell death mediated by iron and acute kidney injury (AKI) is recently gaining widespread attention. However, the mechanism of the crosstalk between cells in the pathogenesis and progression of acute kidney injury remains unexplored. In our research, we performed a non-negative matrix decomposition (NMF) algorithm on acute kidney injury single-cell RNA sequencing data based specifically focusing in ferroptosis-associated genes. Through a combination with pseudo-time analysis, cell–cell interaction analysis and SCENIC analysis, we discovered that proximal tubular cells, macrophages, and fibroblasts all showed associations with ferroptosis in different pathways and at various time. This involvement influenced cellular functions, enhancing cellular communication and activating multiple transcription factors. In addition, analyzing bulk expression profiles and marker genes of newly defined ferroptosis subtypes of cells, we have identified crucial cell subtypes, including Egr1 + PTC-C1, Jun + PTC-C3, Cxcl2 + Mac-C1 and Egr1 + Fib-C1. All these subtypes which were found in AKI mice kidneys and played significantly distinct roles from those of normal mice. Moreover, we verified the differential expression of Egr1, Jun, and Cxcl2 in the IRI mouse model and acute kidney injury human samples. Finally, our research presented a novel analysis of the crosstalk of proximal tubular cells, macrophages and fibroblasts in acute kidney injury targeting ferroptosis, therefore, contributing to better understanding the acute kidney injury pathogenesis, self-repairment and acute kidney injury-chronic kidney disease (AKI-CKD) progression.

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Deciphering Functional Connectivity Differences Between Motor Imagery and Execution of Target-Oriented Grasping - Eunkyung Kim; Woo Hyung Lee; Han Gil Seo; Hyung Seok Nam; Yoon Jae Kim; Min-Gu Kang; Moon Suk Bang; Sungwan Kim; Byung-Mo Oh (Brain Topography, 2023)

Measurement and control of containing-fluorine particulate matter emission during spent pot lining combustion detoxification process - Funian Han; Liang Yu; Xinyun Mo; Lu Zhang; Jiaqi Jia; Jingmeng Dong; Shaopeng Gu (Journal of Hazardous Materials, 2023)

Impact of matrix metalloproteinase-8 gene variations on the risk of thoracic aortic dissection in a Chinese Han population - Xiao-Zeng Wang; Xiao-Mo Du; Quan-Min Jing; Xing-Xing Li; Ruo-Xi Gu; Jiao Wang; Ya-Ling Han (Molecular Biology Reports, 2013)